Confronting Views of Companies and Authorities on Food Safety Issues—A Cross-Country Survey - Djekic, Ilija; Hambardzumyan, Garegin; Nikolić, Aleksandra; Mujčinović, Alen; Nakov, Dimitar; Nikolova, Aleksandra Silovska; Semenova, Anastasia A.; Kuznetsova, Oksana A.; Oz, Fatih; Oz, Emel; Terjung, Nino; Volker, Heinz; et al. (MDPI AG, 2024)
This study investigated food safety issues as perceived by food companies and food safety authorities in six countries in Europe and Central Asia. A total of 66 companies and 16 authorities participated in the survey. The results provide important insights related to what the main food safety priorities are, how they are addressed in the countries that participated in the survey, and what the role of the main stakeholders is in the food value chain. Almost 50% of food companies identified ‘food fraud’ as the most influential food safety attribute. One-third of food safety authorities recognized ‘food safety management system’ as the most influential food safety attribute. Principal component analysis separated food safety statements into two dimensions named ‘food safety hazards and risks’ and ‘food safety system’. Although there are slight differences in food safety statements between the two stakeholders, i.e., food companies and food safety authorities, it is the country of origin that plays a more important role in understanding their views. Food companies will need to implement a systemic approach and transform the entire food value chain continuum while considering new food safety challenges. It is expected that food safety authorities will have to play a more proactive role in the future.
Keywords: food safety; food value chain; food safety integrity; food safety knowledge